Ischia Group Theory 2010: proceedings of the conference : Ischia, Naples, Italy, 14-17 April 2010 - Bianchi Oddera, Mariagrazia (World Scientific, 2012)
Machine generated contents note:Positive Laws on Generators in Powerful Pro-p Groups /G. A. Fernandez-Alcober --Periodic Groups Saturated by Dihedral Subgroups /L. Kazarin --Note on Finite Groups in which the Conjugacy Class Sizes Form an Arithmetic Progression /P. P. Palfy --Survey of Recent Progress on Non-Abelian Tensor Squares of Groups /M. Morigi --Conjugacy Classes of Subgroups of Finite p-groups: The First Gap /R. Brandl --Tutte Polynomial of the Schreier Graphs of the Grigorchuck Group and the Basilica Group /D. Iacono --On Maximal Subgroups of the Alternating and Symmetric Groups /V. Colombo --Markov's Problems through the Looking Glass of Zariski and Markov Topologies /D. Toller --Linear Groups with Finite Dimensional Orbits /J. Otal --Three-dimensional Loops as Sections in a Four-dimensional Solvable Lie Group /A. Figula --Note on Finite p-groups with a Maximal Elementary Subgroup of Rank 2 /
Conference proceedings. - Includes bibliographical references. - Description based on print version record
Keywords: Electronic books; Electronic books -- Conference proceedings; Konferenzschrift